Prekmurske protestantske pesmarice od Mihaela Severa do Janoša Kardoša - Jesenšek, Marko (Slavia Centralis, 2020)
Prekmurian Protestant hymn books from Mihael Sever to Janoš Kardoš The paper presents Prekmurian printed Protestant hymn books from Mihael Sever to Janoš Kardoš. In printed hymn books, Prekmurian Protestants continued the tradition of the Prekmurian manuscript period, especially Martjanske pesmarice I, the oldest preserved Prekmurian handwritten hymn books. Prekmurian Protestants included old Prekmurian hymns, preserved in numerous handwritten hymn books – Škafar (1978) states 61 of those in Bibliografija prekmurskih tiskov – in printed hymn books, corrected them linguistically and disseminated among Slovenes in Prekmurje. In this way, they influenced the formation and development of Prekmurian literary language.